Achieving global equity for COVID-19 vaccines: stronger international partnerships and greater advocacy and solidarity are needed - Figueroa, J. Peter; Hotez, Peter J.; Batista, Carolina; Amor, Yanis Ben; Ergonul, Onder; Gilbert, Sarah; Gursel, Mayda; Hassanain, Mazen; Kang, Gagandeep; Kaslow, David C.; Kim, Jerome H.; Lall, Bhavna; et al. (PLoS medicine, 2021)
Peter Figueroa and co-authors advocate for equity in the worldwide provision of COVID-19 vaccines.
Gesehen am 11.11.2021